Erratum: Ankyrin-mediated self-protection during cell invasion by the bacterial predator Bdellovibrio bacteriovorus - Carey Lambert (Nature Portfolio, 2016)
Nature Communications 6: Article number: 8884 (2015); Published: 2 December 2015; Updated: 21 January 2016. The original HTML version of this Article contained an error in the spelling of the author R. Elizabeth Sockett, which was incorrectly given as Elizabeth R. Sockett. This has now been corrected in the HTML.